The hybrid library: a view from the UK - Pinfield, Stephen (1999)
This paper aims to provide an overview of digital library development in the UK, concentrating on the eLib (Electronic Libraries) programme. It also discusses the idea of the Hybrid Library and considers how it fits into current electronic library developments. The paper is divided into the following areas. First, it summarises the background to the eLib programme and discusses some of its preliminary findings. It then discusses the concept of the Hybrid Library, followed by a summary of the of the current eLib (phase 3) projects which include hybrid library development projects. Finally, it identifies a number of common themes between the different projects which are currently being investigated.